Performance comparison between architectures Ibm z and Ibm power system - Moura, Cássio Félix (2021)
This comparative technical article uses the resources of two important tools in IBM's history, namely: IBM Z and IBM Power System. Both systems are equipped with current technology and use Linux RedHat as an operating system base, equally compiled. In this approach, the performance of the structures is compared using the C language based on a script developed for the test. The results show the response time obtained after the execution, and the hardware resource used to obtain the consolidated data.